2007
DOI: 10.1088/0953-2048/20/6/007
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in the high-Tcphase of BSCCO superconductors by Nb addition

Abstract: Pure and Nb2O5 added Bi1.6Pb0.4NbxSr2Ca2Cu3Oδ superconductors (x varies up to 0.30) were synthesized by the solid state reaction method. Structural and superconducting properties of the samples were investigated. The fraction of the high-Tc phase (2223) increases with Nb addition up to x = 0.10, for which a nearly single 2223 phase was obtained. The critical temperature of the samples increases from 96 to 104 K with doping up to x = 0.20 and a further increase in Nb decreases the Tc sharply. Similarly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Nevertheless, there are few reports on the effects of substitutions to Cu sites in the BSCCO (2223) system. It is recently observed that niobium, vanadium, and titanium addition increases the (2223) phase considerably and succeeded to isolate this phase up to 96% and 97% [17,18]. In this study, we desire to investigate both the effect of the sintering time on the formation of the high T c phase and the effect of other high valency cations like vanadium and titanium.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are few reports on the effects of substitutions to Cu sites in the BSCCO (2223) system. It is recently observed that niobium, vanadium, and titanium addition increases the (2223) phase considerably and succeeded to isolate this phase up to 96% and 97% [17,18]. In this study, we desire to investigate both the effect of the sintering time on the formation of the high T c phase and the effect of other high valency cations like vanadium and titanium.…”
Section: Introductionmentioning
confidence: 99%
“…and Naghshara, H. [11] [12] [13]. Among these phases, the Bi-2223 phase with the chemical formula of Bi 2 Sr 2 Ca 2 Cu 3 O 10+y appears to be suitable for superconducting devices which are operating at a temperature of liquid nitrogen (T > 77 K) [14]. But the formation of pure Bi-2223 phase is a critical issue in fabricating BSCCO superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…It have been produced the (BiPb) 2 Ce x Sr 2 Ca 3 Cu 4-y Ti y O 12+δ compounds for x = 0.05 ve y = 0, 0.05, 0.1, 0.2 by conventional solid state reaction method. The effects of cerium adding and Ti doping on the structure have been investigated by electrical resistance, XRD patterns and magnetic hysteresis loop measurements.…”
Section: Introductionmentioning
confidence: 99%